Relationship between methylation status of PTEN and point mutation of the EGFR L2 domain and efficacy of cetuximab in metastatic colorectal cancer - Ito, Y.; Yamada, Y.; Asada, K.; Ushijima, T.; Iwasa, S.; Kato, K.; Hamaguchi, T.; Shimada, Y. (Journal of Clinical Oncology, 2011)
Abstract only 458 Background: The KRAS mutation has been associated with resistance to cetuximab, an anti-epidermal growth factor receptor (EGFR) monoclonal antibody, in metastatic colorectal cancer (mCRC). However, the predictive biomarkers of cetuximab resistance in KRAS wild-type mCRC remain unknown. We explored the possible roles of PTEN methylation and mutation of the EGFR L2 domain, which is the site of binding to cetuximab, in cetuximab resistance in KRAS wild-type mCRC. Methods: The subjects were 247 mCRC patients screened for KRAS status at the National Cancer Center Hospital between September 2008 and April 2010. Genomic DNA was extracted from formalin- fixed paraffin-embedded colorectal cancer tissue samples. Mutation analysis of KRAS and the EGFR L2 domain was performed by direct sequencing. Methylation analysis of PTEN was performed by quantitative real-time methylation-specific PCR with a set of primers specific to the methylated and unmethylated sequences, using sodium bisulfate-modified DNA. Results: Of the 247 mCRC patients, 136 patients had wild-type KRAS (55%). In 9 of these patients, the quality of the DNA was sufficient for analysis of PTEN methylation levels. Eight of the 9 patients received a cetuximab-based regimen (with irinotecan: 4, monotherapy: 4). The best response was PR in 4 patients (25%), SD in 2 (12.5%), and PD in 2 (12.5%). The best response of the one patient with methylated PTEN treated with cetuximab and irinotecan was SD. Mutation analysis of the EGFR L2 domain was performed in 65 of the 136 patients with wild-type KRAS. All of them received a cetuximab-based regimen (with irinotecan: 50, monotherapy: 15). The best response was PR in 13 patients (20%), SD in 26 (40%), PD in 20 (31%). The one patient who had a mutation at exon 9 showed a partial response to cetuximab and irinotecan. Conclusions: Methylation of PTEN and mutation of the EGFR L2 domain were analyzed in Japanese mCRC patients. Our findings do not provide sufficient evidence that EGFR L2 domain mutation and methylation of PTEN are correlated with resistance to cetuximab. No significant financial relationships to disclose.